Studi Perbandingan Nilai Konduktivitas Termal Gypsum dan Sandwich Panel Sebagai Material Dinding Paint Dry Room - Chandra Dwiaji, Yudhi; Hazizah, Rizka (Indonesian Society of Applied Science, 2024)
PT. XYZ is a company engaged in manufacturing guitar musical instruments. One of the processes in making guitars is the process of painting the guitar body which aims to give color to the guitar body and protect the guitar body from damage to external elements. After the painting, the guitar body must be dried at a certain temperature to get a nice and shiny color result. To fulfill these results, a paint dry room is needed to maintain a room temperature of 42.1°C - 42.5°C, but also does not have a heat impact on the outdoor environment. Currently, there is no standard wall material that can be used as a paint dry room wall. This study uses an experimental method to determine the thermal conductivity of gypsum and sandwich panels, then calculates the thermal conductivity and simulates a comparison with the software. The calculation result based on the thermal conductivity formula is that gypsum has a thermal conductivity of 0.059 [W/m°C] and a sandwich panel thermal conductivity of 0.142 [W/m°C]. This proves that gypsum has better insulating properties than sandwich panels. This study found that gypsum walls are more profitable to be used as paint dry room wall materials.